Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; régions géographiques; sciences humaines; sociologie; systèmes d'oppression; thématiques; travail; émotions

Quadruple défi pour les artistes femmes, immigrantes et allophones : le cas du premier Sarau das Minas Montréal - Vasconcellos de Carvalho, Dalila (Les Cahiers de la Société québécoise de recherche en musique, 2021)
Cet article porte sur le processus de création du premier Sarau das Minas Montréal : une soirée de sororité artistique qui s’est déroulée le 8 mars 2020. Il s’agit d’un événement artistique conçu, dirigé et réalisé par une équipe de femmes, immigrantes et allophones. Cet événement est ancré, d’une part, dans une démarche féministe empirique inductive visant la construction d’une scène sûre pour des artistes femmes immigrantes et allophones. D’autre part, il s’inspire de l’analyse préliminaire des données de ma recherche de doctorat sur les musicien·nes immigrant·es oeuvrant sur le marché de la « musique du monde » à Montréal. La construction d’une scène sûre pour ces femmes implique l’aménagement d’un espace dans lequel elles sont avant tout reconnues et appréciées en tant qu’artistes. En outre, l’analyse des données recueillies montre que le fait d’être à la fois artiste, femme, immigrante et allophone s’impose comme un quadruple défi. En s’inspirant de la notion d’« espace sûr », ce projet événementiel cherchait des réponses pragmatiques à deux problèmes vécus par les artistes femmes immigrantes allophones : leur sous-représentation dans le milieu artistique professionnel québécois et la langue en tant qu’obstacle à leur l’inclusion. Le Sarau résulte ainsi du travail collectif et de la volonté d’un groupe de femmes artistes, immigrantes et allophones entreprenant une démarche d’émancipation vis-à-vis leur propre invisibilité.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; artistes féministes; arts; discipline; espace sécuritaire; femmes* artistes; femmes* immigrantes; intersectionnalité; invisibilité; inégalités; inégalités linguistiques; montréal; musique; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppression; thématiques; travail